Radiation-induced defect's clustering and self-organization during surface modification - Bondareva, A.L.; Zmievskaya, G.I. (Вопросы атомной науки и техники, 2006)
Defects' clustering model is applied to study of the both: helium blistering in metal lattice and a thin film islands
deposition. Plasma surface modification is investigated as a first order phase transition at a fluctuation stage. Wiener
stochastic processes which are associated with the clustering evolution as well as with the defects motion are used.
Brownian motion due to a long-distance potentials of indirect interaction blisters (or islands): through acoustic
phonons and Friedel's oscillations of lattice's electronic density has been modeled. Stochastic simulation has involved
the analyse of a follows self-organization structures: vacancy-gaseous bubbles layers (or porosity) and islands
chains on the surface with roughnesses. Модель кластеризации приложена к изучению: гелиевого блистеринга в металлах и осаждение островковых тонких пленок. Модификация поверхности плазмы исследована как фазовый переход 1-го рода на флуктуационной стадии. Исследован Винеровский стохастический процесс, который ассоциируется с эволюцией кластеризации и с движением дефектов. Промоделировано броуновское движение благодаря дальнодействующим потенциалам непрямого взаимодействия блистеров (или островов): через акустические фононы и Фриделевские осцилляции электронной плотности. Стохастическое моделирование включает анализ следующих самоорганизующихся структур: слои вакансионно-газовых пузырей (или пористость) и неупорядоченные цепочки островов на поверхности. Модель кластерізації прикладена до вивчення: гелієвого блистерінгу у металах та осадженню
острівкових тонких плівок. Модифікація поверхні плазми досліджена як фазовий перехід 1-го роду на
флуктуаційній стадії. Досліджено Вінерівський стохастичний процес, котрий асоціюється з еволюцією
кластерізації та рухом дефектів. Промодельовано броунівський рух завдяки далекодіючим потенціалам
непрямої дії блістерів (або островів): через акустичні фонони та Фриделевські осциляції електронної
густини. Стохастичне моделювання включає аналіз наступних структур самоорганізації: шари вакансійно-
газових пузирів (або пористість) і неупорядковані ланцюги островів на поверхні.